Teaching Law to Accounting and Business Students: A Cumulative Dual Model - Ewang, F. (Journal of University Teaching and Learning Practice, 2008)
This article presents a reflection and comparison of two of my teaching pedagogical approaches for the Business Organisations Law curriculum to undergraduate non-law students at Charles Sturt University. The purpose is to compare and evaluate efficacy of a traditional, lecture-based learning (LBL)i with a combination of LBL and problem-based learning (PBL)ii in improving performance and outcomes for students enrolled in the accounting and business degrees. Research methods to compare outcomes and performances were evaluated using modified versions of several LBL and PBL related survey questionnaires and a Study Process Questionnaire (SPV) developed by John Biggs for use with Australian tertiary students, and validated for use with students in several Asian countries. Data regarding students’ perceptions of LBL and a combination of LBL and PBL were further collected using a 13-point interview questionnaire. Responses from a Likert scale were calculated in percentages and considered in terms of a mean response and data from the qualitative responses coded in NVIVO and analysed thematically. Also, ‘tests scores’ (assignments and final exam results - mostly problem questions) from a traditional LBL class were compared with the scores from a mixture of both LBL and PBL. Though groups’ means of both LBL and PBL were closer, the results combined with other indicia revealed that students studying the course through a combination of both lectures and PBL tutorials in a teaching session performed significantly better. The paper recommends a cumulative dual approach as effective course delivering methods.